Explorando a física na música - Santos, Lelyz (2022)
The present work proposes a didactic sequence together with a low-cost experiment making an interdisciplinarity with music. The application of the product was in a night class of the 2nd year of EJA (Youth and Adult Education) in the period November 2021 during the COVID-19 pandemic, after resumption of face-to-face classes authorized by the government of the State of Amazonas, after eighteen months of face-to-face classes suspended. It brings the relationship between music and sounds through intervals, harmony and other musicalities. The work will have Ausubel as one of the pedagogical foundations for meaningful teaching and learning. It will have a good theoretical basis and the mathematical and physical foundations to support the proposals suggested to high school teachers to easily apply to students, as it will not need laboratories, only good will. Finally, the main objective is to somehow contribute to Brazilian society; physics; teacher/educators and the scientific community.